Kierkegaard's Writings, 21 : For Self-Examination - Kierkegaard, Søren, 1813-1855 (Kierkegaard's Writings., 2015)
For Self-Examination and its companion piece Judge for Yourself! are the culmination of Søren Kierkegaard's ""second authorship, "" which followed his Concluding Unscientific Postscript . Among the simplest and most readily comprehended of Kierkegaard's books, the two works are part of the signed direct communications, as distinguished from his earlier pseudonymous writings. The lucidity and pithiness, and the earnestness and power, of For Self-Examination and Judge for Yourself! are enhanced when, as Kierkegaard requested, they are read aloud. The.